The adverse effect of the herbicide atrazine on the reproduction in the intertidal varunid crab Neohelice granulata (Dana, 1851) - Alvarez, Natalia Belen (2015)
The effects of a 32-d exposure to atrazine (0, 2.5, 5 and 15 mg/L) were evaluated in the estuarine crab Neohelice granulata, both in terms of larvae hatching and ovarian re-maturation. No significant differences (p > 0.05) were detected either in incubation time or the number of hatched larvae per female. However, atrazine, particularly at the two higher concentrations, caused several larval abnormalities including hydropsy, hyperpigmented body, atrophy of spines and setae, and atrophy of eyes. At the end of the 32-d exposure period, all assayed atrazine concentrations produced a significant (p < 0.05) reabsorption of previtellogenic oocytes, compared to the control treatment. Although no changes in the gonadosomatic index were detected (p > 0.05), the proportion of vitellogenic oocytes decreased at all atrazine concentrations, reaching significance at 5 mg/l (p < 0.05). These results highlight the potential risk of atrazine for crustacean reproduction, both in terms of altered ovarian maturation and abnormal hatched larvae.